2011
DOI: 10.1007/s11434-011-4603-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous nannofossil bioevents and microtektite stratigraphy in the Western Philippine Sea during the Quaternary

Abstract: Two sediment cores, MD06-3050 and MD06-3047, were analyzed to study the Quaternary calcareous nannofossil and microtektite records. We dated bioevents and the microtektite impact event by calibrating with oxygen isotope stratigraphy. Seven calcareous nannofossil bioevents were identified over the past 2.36 Ma including the last appearance of data for Discoaster brouweri, Calcidiscus macintyrei, large Gephyrocapsa and Pseudoemiliania lacunosa, the first appearance of data for large Gephyrocapsa and Emiliania hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Therefore, the study core spans Marine Isotope Stages (MIS) 1-17, thus recording the paleoceanographic history of the last 696 ka with an average time resolution of 0.78 ka/cm. Besides, the validity of this chronology has also been confirmed by identification results on calcareous nannofossil bioevents [16].…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, the study core spans Marine Isotope Stages (MIS) 1-17, thus recording the paleoceanographic history of the last 696 ka with an average time resolution of 0.78 ka/cm. Besides, the validity of this chronology has also been confirmed by identification results on calcareous nannofossil bioevents [16].…”
Section: Resultssupporting
confidence: 55%
“…It contains continuous sedimentation with no obvious gap or abrupt interruption. For the study core is located above the lysocline (3400 m) therein, carbonate is well preserved in the study core [16].…”
Section: Geological Setting and Samplesmentioning
confidence: 95%
“…The first appearance of Em. huxleyi has subsequently been placed between 0.262-0.264 Myr (Sun et al, 2011). Okada (2000) found a rapid and abrupt alteration of the flora in the earlier Pleistocene and concluded that the waters overlying Site 994 fluctuated between oligotrophic gyre waters with strong stratification and mesotrophic gyre margin waters with moderate upwelling events.…”
Section: Site Descriptionmentioning
confidence: 99%
“…This indicates a depositional rate of 3.5 cm/ka in the uppermost part of the Hole. The first appearance of E. huxleyi has subsequently been placed between 0.262–0.264 Myr [34].…”
Section: Site Descriptionmentioning
confidence: 99%